Nasal Congestion and Its Management in Pregnancy Rhinitis - Niken L. Poerbonegoro (Indonesian Socety of Obstetrics and Gynecology, 2019)
Background: Pregnancy rhinitis occurs approximately in one-fifth of pregnancies, at almost any gestational week. The incidence rate of pregnancy rhinitis reaches up to 40%, with prevalence as high as 17%. Pathomechanism is still unclear, but it is suspected that estrogen and placental growth hormone (PGH) play roles in the development of disease. Objective: To elaborate the pathomechanism of pregnancy rhinitis and the proper management of rhinitis symptoms, particularly nasal obstruction. Methods: Literature review. Conclusion: Pregnancy rhinitis, manifested as nasal congestion, is considered a phenomenon and may become a serious condition. Persistent nasal congestion acts as a potential risk factor in affecting fetal growth and development through gradual hypoxia process. This condition can lead to various complications such as maternal hypertension, preeclampsia, impaired fetal growth, and low APGAR scores. Indepth knowledge of pathomechanism is essential as guidance to accurate treatment including conservative and pharmaca therapies, which will lead to optimal outcome for both mother and baby.